China Weeps: The Opium Wars and Chinas Stolen History. Issue 1 (March 2015) - Blessing, Olivia L E.
In the mid-1700s, the relationship between the British Empire and Imperial China began to collapse over a series of cultural, economic, and ethical conflicts which would result in the First (1839-1842) and Second (1856–1860) Opium Wars—tumultuous events that would have a devastating and humiliating impact on Chinese history. The looting of the Yuanmingyuan Summer Palaces during the Second Opium War was a tragedy that would be as destructive to Chinese culture as the wars' resulting treaties were to its territorial borders. Today, the Chinese continue to dispute the morality of both the wars and the subsequent looting of their Summer Palaces. It is thus unsurprising, then, that modern China has undertaken great effort to recover the artifacts from the Summer Palaces. While some of these attempts have been largely unsuccessful, it is clear that China will continue to pursue repatriation of lost relics. This struggle provides an excellent opportunity for examining both China's modern approach to cultural heritage preservation and the potential problems existing in international laws hindering the protection of cultural resources throughout the world.